O pioneers! (Great Plains Trilogy, ,, 2001)
Swedish farmer John Bergson's daughter Alexandra encourages the family members to help keep his dream alive after his death.

Death comes for the archbishop (Vintage classics, ,, 2016)
The story of a French priest who goes to New Mexico and, with another priest, wins the Southwest for the Catholic Church. After forty years, he dies--the archbishop of Santa Fe.
Prologue. At Rome , The Vicar Apostolic , Missionary journeys , The mass a Ácoma , Snake root , Padre Martínez , Doña Isabella , The great diocese , Gold under Pike's Peak , Death comes for the archbishop.

Shadows on the rock (Borzoi book, ,, 1951)
At the end of the 17th century in Quebec, Cecile Auclair and her father, the town's apothecary, live a life very different than the one they knew in Paris. They spend the winter with no word from home. But Cecile does not feel exiled, for as old ties die, new ones are formed.